Non-Ionizing radiation burns (NIRB): Impacts and protection measures in the work environment (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
This scientific paper focuses on non-ionizing radiation (NIR), a form of electromagnetic radiation that, although it does not have enough energy to ionize atoms or molecules, can convert its energy into heat and cause burns. Exposure to excessive levels of NIR can be harmful, especially for those who work with devices and instruments that generate large amounts of NIR. Examples include radiofrequency radiation used in telecommunications and microwaves used in home cooking. Exposure to ultraviolet (UV) radiation can be beneficial in small doses, but excessive exposure can cause skin burns and increase the risk of skin cancer. Intense exposure to radiofrequency (RF) or microwave radiation can cause tissue damage due to heat. The use of personal protective equipment, such as protective clothing, UV-rated eye and face protection, and gloves, can help minimize these risks.
Keywords: Radiación no ionizante (NIR); Radiación de radiofrecuencia, Radiación ultravioleta (UV); Equipo de protección personal